All Days 2007
DOI: 10.2118/107760-ms
|View full text |Cite
|
Sign up to set email alerts
|

Acid Stimulation of Extended Reach Wells: Lessons Learnt From N'Kossa Field

Abstract: fax 01-972-952-9435. AbstractN'Kossa is an offshore field located 60 km west of the coasts of Congo in water depths of 170 m. The field is producing light sweet oil from an Albian age reservoir buried between 3100m and 3400m TVD. In order to access reserves located in the southernmost compartments of the reservoir, Extended Reach Drilling (ERD) was implemented. Six ERD wells have been drilled to date with lateral extensions close to 6500 m leading to total depths sometimes in excess of 8600m. In addition to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In some cases, a combination of pumping techniques and diversion mechanisms is implemented to achieve the desired outcome. For instance, Mazel et al (2007) showed how a combination of CT pumping and annular bullheading, along with the use of ball sealers, was necessary to efficiently stimulate an extended reach well. Under similar conditions, Jorden et al (2011) preferred the sole use of CT, along with a specially designed jetting nozzle, which was reciprocated in front of the interval to be stimulated.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, a combination of pumping techniques and diversion mechanisms is implemented to achieve the desired outcome. For instance, Mazel et al (2007) showed how a combination of CT pumping and annular bullheading, along with the use of ball sealers, was necessary to efficiently stimulate an extended reach well. Under similar conditions, Jorden et al (2011) preferred the sole use of CT, along with a specially designed jetting nozzle, which was reciprocated in front of the interval to be stimulated.…”
Section: Introductionmentioning
confidence: 99%